Taâlimu al-MahÄrat al-QurÄniyyah - Anshori, Ahmad Suyuti (Al-Jamiah: Journal of Islamic Studies, 2004)
The quran is the great miracle of the prophet Muhammad saw. The book is absolutely holy, far from any distortion as underwent by other holy books. The Quran book is the most authentic source book ever given to human civilization. Nowadays no scholars or linguist could imitate the beauty and then compact quality of the Qurâan. In addition, the Qurâan has also made a significant contribution to Arabic language and also its eternity. Thanks to the book, the Arabs became one community, and Muslims could unearth on knowledge. Therefore, the Qurâan has become the central point for Muslims from the time of the Prophet to our recent area. A number of religious scholars, researchers, and writers have focused their attention on the holy book, from way how to read, write, memories, interpret, and study its miracle. This writing elaborates on the way how to teach skill about the Quran i.e., listening, writing, reading, and memorizing-all in relation to various theories of education.